2015
DOI: 10.4028/www.scientific.net/amm.770.40
|View full text |Cite
|
Sign up to set email alerts
|

New Multilayer Corrosion Resistant Materials for Nuclear Power Engineering

Abstract: The authors developed a new class of multilayer materials that feature high corrosion resistance in halogenide-containing media. Corrosion resistance is provided by the multilayer structure. The principle of “sacrificial pitting protection” was formulated. The corrosion resistance tests were carried out. Explosive welding technology was introduced for fabrication of multilayer materials. It is suggested to use the multilayer materials as a structural material in construction of reservoirs for liquid radioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…At present, materials for nuclear power engineering have limited operational characteristics, which do not allow one to maximally fully realise the potential of power plants of new generation [1,2]. The material of shells of heat-producing and other responsible elements of the active zone of fast neutrons reactors of new generation, working in mode of the closed nuclear fuel cycle, must provide their reliable and safe operation during maximal fuel burn-out up to 20% of heavy atoms with a damaging dose up to 180…200 dpa at temperatures of 370…700 ºС and have the long-term strength of σ 10000 600 ≥ 100 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, materials for nuclear power engineering have limited operational characteristics, which do not allow one to maximally fully realise the potential of power plants of new generation [1,2]. The material of shells of heat-producing and other responsible elements of the active zone of fast neutrons reactors of new generation, working in mode of the closed nuclear fuel cycle, must provide their reliable and safe operation during maximal fuel burn-out up to 20% of heavy atoms with a damaging dose up to 180…200 dpa at temperatures of 370…700 ºС and have the long-term strength of σ 10000 600 ≥ 100 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Obtainment of materials, meeting the mentioned characteristics, namely possessing high heat resistance simultaneously with high radiation and corrosion resistance, is a relevant practical task. Works [1][2][3] demonstrated that the most promising material for fast neutrons (hereinafter FN) reactors was alloys based on vanadium, titanium and chromium. Enhanced operational characteristics (high strength and radioresistance) belonged to alloy V-4.9Ti-4.8Cr, obtained by the method of powder metallurgy [3,4] and recommended for using in nuclear power engineering.…”
Section: Introductionmentioning
confidence: 99%
“…These materials significantly decrease the cost of metal constructions, however, the term and reliability of exploitation thereof entirely depend on corrosion resistance and cladding layer thickness. Instead of monometallic materials and bimetals the authors suggest to use a composite multilayer corrosion resistant material featuring the realized principle of "sacrificial pitting protection" [1,2,3]. The heterogeneous structure provides resistance of the multilayer material in conditions of pitting corrosion.…”
Section: Introductionmentioning
confidence: 99%